Diagnostic, preventive and therapeutic evidence in obstetrics for the implementation of patient blood management: a systematic review protocol - Abraha, Iosief (BMJ Open, 2018)
INTRODUCTION: Patientblood management (PBM) is defined as the application of evidence-based diagnostic, preventive and therapeutic approaches designed to maintain haemoglobin concentration, optimise haemostasis and minimise blood loss in an effort to improve patient outcome. We propose a protocol for the assessment of the evidence of diagnostic, preventive and therapeutic approaches for the management of relevant outcomes in obstetrics with the aim to create a framework for PBM implementation. METHODS AND ANALYSIS: Diagnostic, preventive and therapeutic tools will be considered in the gynaecological conditions and obstetrics setting (antenatal care, peripartum care and maternity care). For each condition, (1) clinical questions based on prioritised outcomes will be developed; (2) evidence will be retrieved systematically from electronic medical literature (MEDLINE, EMBASE, the Cochrane Library, Web of Science, and CINAHL); (3) quality of the reviews will be assessed using the AMSTAR (A Measurement Tool to Assess Systematic Reviews) checklist; quality of primary intervention studies will be assessed using the risk of bias tool (Cochrane method); quality of diagnostic primary studies will be assessed using QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies); (4) the Grading of Recommendations Assessment, Development and Evaluation method will be applied to rate the quality of the evidence and to develop recommendations. ETHICS AND DISSEMINATION: For each diagnostic, preventive or therapeutic intervention evaluated, a manuscript comprising the evidence retrieved and the recommendation produced will be provided and published in peer-reviewed journals. Ethical approval is not required.